The Filipino struggle for intellectual freedom - Garcia, Fe Gasillan (Education quarterly.)
This paper reviews the Filipino struggle for intellectual freedom from the Spanish occupation to the modern era. This struggle has always been an uphill battle due to psychological and socio-economic constraints. However, the Filipino spirit is undaunted, it tries to break loose from the fetters that bind it.